(untitled) (Al-Academy, 2023)
The current research deals with the study of aesthetic relations in the field of interior design and the extent to which its mechanisms achieve sensory stimulation between the internal and external spaces, to generate a continuous visual connection that is an extension of it, achieving in turn sensory stimulation for the users of those spaces. The internal and external spaces meet the desired purpose of feeling pleasure and beauty.” The current research aims to “discover the nature of aesthetic relations between the internal and external spaces and the extent to which mechanisms can achieve sensory stimulation in residential spaces.” The first topic included the concept of aesthetic relations, sensory excitement, and perception at the level The relationship between the part and the whole on the one hand, and sensory stimulation and the laws of perceptual organization according to the Gestalt laws on the other hand, while the second topic dealt with the concept of external spaces and internal spaces and their borders, leading to the third topic that dealt with the aesthetic relations between the inside and the outside with applications for global internal spaces of the type (outdoor living room ) for the living space in the residential building in a way that secures closeness to the aesthetic completion of relations and arouses in the recipient a sense of pleasure and attraction, which made the designers emphasize working according to this type of space according to modern technologies of our current era and at the level of material and lighting. The research reached a set of conclusions, which It represented an objective analysis of the aesthetic relationships that make sensory excitement achievable in interior design, including:1-Aesthetic relations were embodied through unity and repetition in the use of plants that achieve sensory stimulation at the level of the principle of perceptual organization (gestalt), through the principle of convergence between the external and internal spaces by employing green plants to enhance belonging to each other, as well as the principle of convergence in the employment of environmentally friendly materials in the furnishing elements. to enhance unity.2-Visual equilibrium contributes to achieving sensory excitement through varying the degree of transparency and what it achieves of openness through continuity and an extension of visual penetration between the external and internal spaces and in a smooth manner, by employing transparent materials such as glass in the facades, walls and barriers overlooking the outside in a continuous manner.